Advanced Microfluidic Biofuel Cells Using Gold and Silver Leaf on Paper and PDMS Substrates: Toward Implantable Energy Solution - S. Vanmathi; Sanket Goel (IEEE Journal of the Electron Devices Society)
An exploration of new and simplified electrode materials such as gold leaf (GL), and silver leaf (SL) based approaches to enhance the efficiency and scalability of microfluidic biofuel cell renewable energy sources has generated significant interest. Our research aims to utilize the unique properties of these materials to create advanced biofuel cells, with a specific focus on implantable devices. By employing nanoporous gold and patterned silver leaf, are designing flexible, efficient, and scalable biofuel cells that have the potential to revolutionize energy solutions in medical and wearable technologies. Microfluidic biofuel cells with nanostructured gold and silver leaf devices harvest ultra-low power energy, making them more practical for real-world applications. The gold and silver leaf enzymatic biofuel cell (LEBFC) operates using glucose as fuel, with glucose oxidase functioning at the anode and laccase at the cathode, both coating the GL and SL bioelectrodes. These leaf microfluidic devices, fabricated using polydimethylsiloxane (PDMS) and filter paper, demonstrated a peak open circuit voltage of 197 mV and 448 mV, along with a maximum power density of $28.7 μ ~W / cm^2$ and $93.6 μ ~W / cm^2$ , respectively. Such flexible devices are lightweight, non-toxic, edible, and biodegradable, designed for optimal load connection to ensure stable performance while reducing weight. Please replace with this sentence. It opens new opportunities for sustainable power generation and offers promising applications in wearable, implantable, and portable microelectronic devices, where reliable, low-power energy sources are inexpensive.